Helmintofauna de Leptodactylus syphax (Anura: Leptodactylidae) do bioma da Caatinga, Nordeste do Brasil - Lins, Aline Gouveia De Souza [UNESP]; Aguiar, Aline [UNESP]; Morais, Drausio Honorio; Firmino Da Silva, Lidiane Aparecida [UNESP]; Ávila, Robson Waldemar; da Silva, Reinaldo José [UNESP] (FapUNIFESP (SciELO), 2017)
Leptodactylus syphax is distributed in central, southeastern and northeastern Brazil, eastern Bolivia and southern Paraguay, occupying open areas and rock outcrops, in rock cavities and termite burrows. We collected 21 frogs from the Caatinga region of the state of Ceará, northeastern Brazil, and 7,021 helminths were recovered from 18 of these hosts (overall prevalence = 85.7%). Six helminth taxa were recovered, as follows: Aplectana membranosa (n = 3,756); Schrankiana formosula (n = 3,176); larvae of Physaloptera sp. (n = 43); unidentified nematode larvae (n = 7); digenean metacercariae of Lophosicyadiplostomum sp. (n = 2); and cystacanths of Acanthocephala (n = 37). The similarity of helminth composition between L. syphax from the Caatinga and other species of the L. fuscus group showed that some anurans were clustered according to parasite species and others according to geographic locality. This study presents new helminth records for the Neotropical region, thus helping in understanding the pattern of species distribution, and it increases the knowledge of parasites associated with amphibians.
Helminth fauna of Leptodactylus syphax (Anura: Leptodactylidae) from Caatinga biome, northeastern Brazil
Keywords: Caatinga; Helminths; L. syphax; Leptodactylus fuscus group; Parasites